Three dimensional reconstruction of the left ventricle from multiple cross sectional echocardiograms. Value for measuring left ventricular volume. Issue 5 (November 1983) - Sawada, H; Fujii, J; Kato, K; Onoe, M; Kuno, Y
Abstract : The accuracy of a system for reconstructing a three dimensional image of the left ventricle from randomly recorded multiple short axis images was tested by comparing the calculated left ventricular volume with the directly measured left ventricular volume in 11 excised porcine hearts. The system comprised a real time phased array sector scanner, a transducer locating system, and a computer system for digitising outlines of the left ventricle, displaying the reconstruction image, and calculating the left ventricular volume. The reconstructed image was similar to the real image and the calculated left ventricular volume showed a high correlation with the directly measured left ventricular volume. This method was accurate in vitro and is expected to be available for clinical measurement of left ventricular volume.